COVID-19 Morbidity Among Oral Health Professionals in Brazil - Raquel Conceição Ferreira; Viviane Elisângela Gomes; Najara Barbosa da Rocha; Lorrany Gabriela Rodrigues; João Henrique Lara do Amaral; Maria Inês Barreiros Senna; Gizelton Pereira Alencar (Elsevier, 2022)
ABSTRACT: Background: We evaluated and compared the cumulative incidence of confirmed COVID-19 cases between oral health professionals and the general population in Brazil. Methods: Secondary data from notification of laboratory unconfirmed and confirmed cases of COVID-19 in the National data system for 41 epidemiological weeks were analysed and compared between oral health professionals (dentist + oral health technicians/assistants) and the general population. The cumulative incidences of COVID-19 were obtained by the ratio of the total number of confirmed cases to the total Brazilian population or the population of oral health professionals registered with the Federal Council of Dentistry and adjusted by age. The incidences were then compared. Results: The age-standardised cumulative incidences were 18.70/1000 for oral health professionals and 17.71/1000 for the population, with a ratio of 1.05. The highest incidences were observed in the states of Roraima (67.05/1000), Tocantins (58.81/1000), and Amazonas (58.24/1000). In 14 states, the age-standardised cumulative incidences were higher among oral health professionals than in the general population. There was a decrease in the number of new cases between the 29th and 30th epidemiological weeks in both populations. Conclusions: COVID-19 infections among oral health professionals was similar to that of the general population. However, the cumulative incidence was 5% higher among oral health professionals, varying among Brazilian states. Practical implications: Infection control practices might help lower the risk of contamination in dental settings.